E-learning readiness among faculty members of medical sciences universities and provide strategies to improve it - Sousan Houshmandi; Eisa Rezaei; Javad Hatami; Behnam Molaei (Tabriz University of Medical Sciences, 2019)
Background: The competence of faculty in conducting e-learning is one of the preconditions for e-learning implementation in a university. This study aimed at investigating the readiness of the faculty members of Ardabil University of Medical Sciences (ARUMS) to have e-learning. Methods: To fulfil this purpose, a triangulation method has been used. In the quantitative section, based on the Technological Pedagogical Content Knowledge (TPACK) model, the faculty competence in conducting e-learning has been measured in four areas: pedagogical knowledge, technological knowledge, content knowledge, and finally the skill of combiningpedagogical knowledge, technological knowledge, and content knowledge. Subsequently,with the qualitative data of the semi-structured interview, the findings of the research have been explained. Finally, the strategies for improving the readiness of ARUMS faculty have been identified in e-learning. Results: One-sample t test with a significant level (P ≤ 0.5) showed that the faculty e-learning of ARUMS had the highest mean of pedagogical knowledge, content knowledge and content pedagogical knowledge respectively. In other words, the faculty had a high level of pedagogical,content and content-pedagogical knowledge, but they need to improve their technological,technological-content, technological-pedagogical and ultimately, technological-pedagogical content knowledge. Conclusion: That is why, in order to have effective e-learning at ARUMS, the faculty has to improve their technological, technological-content, technological-pedagogical and technological-pedagogical-content knowledge. In this regard, several solutions have been proposed in this paper.